INVESTIGATION OF STRUCTURAL PROPERTIES OF ALUMINUM NITRIDE USING FIRST PRINCIPLES CALCULATION - Abdulsalam, Mahmud; Shuaibu, Suleiman (FUDMA JOURNAL OF SCIENCES, 2020)
Group-III nitrides have received extensive attention because of their outstanding properties leading to different technological application. It is therefore important to conduct an accurate and systematic theoretical study of the structural properties of one of the important member of these materials. In this work, we studied the structural properties which include the convergence test, convergence of a plane wave cutoff energy, convergence test result with respect to k-points and lattice structural parameter .Our calculations of the structural properties of Aluminum nitride (AlN) were studied using first principle theoretical investigation of the AlN based on density functional theory (DFT) calculation within the generalized gradient approximation (GGA) which was used in the exchange correlation functional as implemented in quantum espresso. Obtained results are discussed within the employed theoretical methods of calculations. Result suggests that, the structure was successfully converged at the cut off-energy of -48.36054179 Ry. Also 45.0 Ry was also found to be as the Kinetic energy cut-off of the plane wave basis set in this research. Furthermore, 4x4x2 k-point was used as the k-point obtained in this research based on Monkhost and pack method of selecting k-point as implemented in (DFT).  The equilibrium value of the lattice parameter obtained at the point of minimum energy is about 3.95 Çº which are in good agreement with experimental value which was 4.05Çº. The deviation of result as shown in figure 4.5 from the experimental result is about 0.1Çº of absolute error which is equivalent to 2.5% of relative error, this shows that
Keywords: DFT, GROUP-III NITRIDES, STRUCTURAL PARAMETER, GGA